National Data Center Innovation Strategy To Build Sustainable Big Data Governance In Indonesia - Wahyumardi, Wahyumardi; Miranda, Agustinus; Zulkifli, Zulkifli (Greenation Research & Yayasan Global Resarch National, 2026)
National Data Center Innovation Strategy to Build Sustainable Big Data Governance in Indonesia. Indonesia’s digital transformation is accelerated through the establishment of the National Data Center as the core infrastructure for integrated government data management. This study aims to analyze innovation strategies required to build sustainable big data governance in Indonesia. The research object focuses on policy frameworks and implementation mechanisms of the National Data Center in supporting cross-agency data integration. A qualitative descriptive approach was employed through policy document analysis and literature review on data governance and cybersecurity. The findings indicate that national data center consolidation enhances interoperability, improves public service efficiency, and supports data-driven decision-making. However, major challenges include limited digital human resources, budget constraints, and cybersecurity vulnerabilities. Recommended strategies involve strengthening human resource capacity, reforming regulatory governance, implementing comprehensive risk and crisis management, and reinforcing data security architecture. Effective and sustainable integration of the National Data Center is essential to achieve accurate, transparent, and adaptive public services in the era of big data.